2014
DOI: 10.4161/rna.35508
|View full text |Cite
|
Sign up to set email alerts
|

Mir-23a and mir-125b regulate neural stem/progenitor cell proliferation by targeting Musashi1

Abstract: Musashi1 is an RNA binding protein that controls the neural cell fate, being involved in maintaining neural progenitors in their proliferative state. In particular, its downregulation is needed for triggering early neural differentiation programs. In this study, we profiled microRNA expression during the transition from neural progenitors to differentiated astrocytes and underscored 2 upregulated microRNAs, miR-23a and miR-125b, that sinergically act to restrain Musashi1 expression, thus creating a regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 31 publications
0
24
0
1
Order By: Relevance
“…The let‐7c miRNA was described as an essential regulator involved in the progress of embryo development (Lin et al, ). Similarly, miR‐23a regulates cellular maintenance and differentiation in mouse embryonic stem cells (Gioia et al, ). Among the already mentioned miRNAs, miR‐96, let‐7c, and miR‐23a were identified in the human placenta of in vivo and successful pregnancies (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The let‐7c miRNA was described as an essential regulator involved in the progress of embryo development (Lin et al, ). Similarly, miR‐23a regulates cellular maintenance and differentiation in mouse embryonic stem cells (Gioia et al, ). Among the already mentioned miRNAs, miR‐96, let‐7c, and miR‐23a were identified in the human placenta of in vivo and successful pregnancies (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify molecular cargoes in astrocyte-derived sEVs able to promote morphological changes in neurons, we took advantage of a comprehensive study by Jovičić et al identifying miRNAs in total homogenates from cultured astrocytes [33]. To generate a robust short-list of candidates, we selected the most abundant miRNAs (cycle threshold < 25), which have been confirmed to be present in astrocytes by at least one other independent study [13,[34][35][36][37][38][39][40][41][42]. Then, the identified candidates, namely miR-26a5p, miR-23a-5p, miR-223a-5p, miR-19a-5p, miR-32a-5p, miR-146a-5p, miR-181-5p, and miR-29a-5p, were categorized using a selection algorithm according to the function of their predicted targets (see Methods; Figure 3A).…”
Section: Astrocyte-derived Sevs Carry Mir-26-5p Which Targets Gene Ementioning
confidence: 99%
“…It has been estimated that more than one-third of all protein-coding genes seem to be miRNA targets in humans by conserved seed pairing [12]. A growing body of evidence has revealed that miRNAs are involved in diverse physiological processes, such as development [13], cell proliferation and differentiation [14, 15], apoptosis [16], and a variety of pathological conditions [17, 18]. Similarly, recent studies have also focused on the involvement of miRNAs in virus-host interaction networks.…”
Section: Introductionmentioning
confidence: 99%